Scientific-practical cooperation of Sytenko Institute and the Eupatoria Resort for Reparative-Restorative Treatment of Children with Orthopaedotraumatic Pathologies - Yaremenko, Dmytro; Korolkov, Oleksandr; Shevchenko, Olena (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article elucidates significance of many years of creative cooperation between scientists of Sytenko Institute of Spine and Joint Pathology and workers of sanatoria of the Eupatoria health resort in the development of scientific-methodological base, improvement and efficacy increase of the restorative sanatorium-and-spa stage in treatment of children with orthopaedotraumatic pathologies. The authors describe the part of the Institute in training skilled medical personnel for physical rehabilitation of children with consequences of injuries, congenital and acquired diseases of the locomotor system in health resort conditions. Prospects for development of scientific-practical cooperation between the Institute and establishments of the Eupatoria health resort are outlined.